Cloud Computing: A Threat or a Boon for Government Administration in the Digital Age? - Yassine, Chami (Estudiante Law Journal, 2025)
The implementation of cloud computing in government administration in the digital era presents both opportunities and challenges. This technology offers a range of benefits, including enhanced operational efficiency, cost savings, improved inter-agency collaboration, and the provision of public services in a faster and more transparent manner. Cloud computing enables centralized data management and real-time access to information, thereby supporting digital government (e-government) initiatives. However, its application also introduces risks related to data security and the privacy of highly sensitive information, such as citizens’ personal data and critical information pertaining to government policies. Dependence on third-party cloud service providers exacerbates the threat to data sovereignty and increases the risk of unauthorized access. This study aims to explore the benefits and challenges faced by governments in implementing cloud computing and to identify mitigation measures that can be adopted to ensure robust data protection. The methodology employed in this study is normative, involving an analysis based on literature, legal regulations, and policies related to cloud computing and data protection in the public sector. The study examines the regulations, policies, and best practices implemented by several countries in managing government data stored in the cloud. The findings reveal that although cloud computing offers efficiency and ease in data management, challenges related to data security, privacy, and dependence on cloud service providers must be addressed with clear policies and stringent security systems. With appropriate policy implementation, cloud computing can be a boon for government administration; however, if not managed carefully, it may pose a threat to public data security